CALL Design Processes in the Indonesian and Australian Universities: Practical Advice on Co-Design Capabilities in the Post-digital Futures - Mustikasari, Dewi Wahyu; Kusuma, Lyla Anggerwina (UIN Salatiga, 2024)
This paper discusses the authors’ personal reflective notes in designing Computer Assisted-Language Learning (CALL) task design for English language teaching for the students in both Indonesian and Australian universities. The multiple case study was employed to see the different TPACK competence, and also social, economic, and geographical backgrounds of both universities. The authors brought together their teacher design practices at the classroom level and their roles in a team design aimed to analyse the design processes using two fields of study perspectives: Learning Design and CALL. Therefore, the classroom observation and reflection teaching journal were used as data to answer a specific case of CALL task design which focused on viewing the CALL task and learning design of English language university teachers, a model drawn on the field of Learning Design, developed by Mustikasari et al. (2022). The cross-case analysis of both universities found out that the University Culture of Leadership Commitment and students’ partner were suggested to escalate the English learning quality and value in post digital world.